SELF-ESTEEM AMONG ADOLESCENTS BASED ON GENDER, EDUCATION AND CASTE - Rathaur, Nidhi; Kumar, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is aimed at finding Self-esteem among adolescents of Muzaffarpur district of Bihar based on gender, education and caste. Hypothesis testing research design is adopted for this study. Data is collected from 50 male and 50 female adolescents studying in different colleges of Muzaffarpur district of Bihar. Convenient sampling techniques is used and data is analyzed with SPSS. Results of analysis revealed that self-esteem level is above average and more self-esteem is reported in female as compared to male adolescents. it is concluded that there is no significant difference in Self-esteem based on education level among adolescents of Muzaffarpur district of Bihar. It is also concluded that there is no significant difference in Self-esteem based on caste among adolescents of Muzaffarpur district of Bihar.